From Paper-Based to Digital Assessment: Adoption and Challenges of Learning Evaluation Applications in Islamic Education - Nurohmah, Eka Yuliana; Ma'rifah, Siti (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
The digital transformation of education has significantly altered the landscape of learning assessment, including in Islamic Education (PAI). The transition from traditional paper-based assessments to digital evaluation methods through various applications has become an emerging trend. However, despite these advancements, the adoption of digital assessment tools among PAI teachers remains inconsistent. This study investigates the extent of adoption and the challenges PAI teachers face in utilizing digital learning assessment applications in Blitar Regency, Indonesia. Employing a quantitative-descriptive research design, data were collected through surveys and interviews with PAI teachers. The findings reveal that 90.9% of respondents have integrated digital assessment applications into their teaching practices, with Google Forms (90.9%), Quizizz (45.5%), Kahoot (36.4%), and Zipgrade (9.1%) being the most commonly used platforms. Several factors influence the adoption of these technologies, including accessibility, ease of use, efficiency, and the ability to generate objective learning outcome data. However, challenges such as limited technological proficiency, inadequate training, and insufficient infrastructure hinder broader implementation. These findings underscore the need for targeted professional development programs and institutional support to enhance digital assessment adoption in Islamic education. This study contributes to the growing discourse on digital learning transformation by providing empirical insights into the opportunities and barriers associated with integrating digital assessment tools in Islamic educational settings